Saftey Management in Construction Project - Ismael A. J. Al-Mashhadani (Genius Journals, 2022)
Currently, both in Iraq and in developed countries, civil construction continues to stand out as one of the most problematic sectors with regard to accidents at work. In Iraq, the sector is the fourth largest generator of fatal accidents in terms of frequency and the second in terms of the coefficient per hundred thousand workers1. In Iraq, the private construction project segment does not yet act as a pressure factor, since the exclusive use of state insurance (which imposes an equal rate for all companies) is predominant, contrary to what occurs in the countries mentioned, in which Insurance is controlled by the private sector and calculated based on indicators that reflect the real age of each company
Keywords: Iraq; company; exclusive; controlled